Bioakumulasi Ion Logam Kadmium Oleh Fitoplankton Laut Tetraselmis chuii dan Chaetoceros calcitraus - Sjahrul, Muhammad; Arifin, Arifin (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2010)
The use of the marine phytoplankton, Tetraselmi chuii and Chaetoceros calcitrans have already been reported. The relationships of the usefulness as phytoremidiator on cadmium polluted marine are not yet well understood. Therefore, this study was conducted to evaluate the influence of Cd2+ addition on fitoplankton medium towards the growth, interacting time, pH medium that could accumunlate Cd2+ in the function groups involved in the bioaccumulation prosess of Cd2+ by phytoplankton. The method of the analysis and the data collectionwas carried out on (1) the growth acceleration, the number of phytoplankton cells, and the chlorophyl-a content; (2) the Cd2+ content in phytoplankton on various interacting time, and pH medium; and (3) the infra-red spectrum of phytoplankton biomass before and after the interaction with Cd2+. The addition of Cd2+ on T. chuui medium can decrease the growth and content of chlorophyll-a, while the addition of Cd2+ on C. Calcitrans medium can increase the growth and content of chlorophyl-a. The phytoplankton can accumulate Cd2+ in the pH8 in the interacting time of 15 minutes with the optimal accumulating ability of 13.46 and 1, 055.27 mg Cd2+ per gram of T. chuii and C. Calcitrans biomasses successively. The function groups of T. Chuii involved in the bioaccumulation process of Cd2+ are-OH, CN, S=O, N-O, S-S and M-S, while on C. Calcitrans, the function groups are-OH, C=0, S-S, M-S and C=C. Keywords: Bioaccumulation, Kadmium, Tetraselmis chuii, Chaetocer calcitrans Key